Public School Trabenco: theadventure of learning - Rafael Feito Alonso; Victor Soler Penadés (Universidad de La Rioja, 2013)
This paper tries to explain the internal working of an infant and primary state school based on data gathered after intensive research at school by the authors themselves. Participant observation of life in classrooms, all kinds of meetings (children committees, school council, staff, pedagogical coordination meetings), arrival and departures of pupils and their families, playgrounds, refectory and so on have been examined. Likewise group discussions with pupils (even pupils at the nearby secondary school with former Trabenco students) and with their parents have been made. Most of the staff has been interviewed as well. In addition documents produced by the school, minutes from meetings and its Web have been under scrutiny. Distribution of school spaces, main traits of learning-teaching processes, its staff, pupils and parents opinions and how to evaluate have been analyzed.